USING DIGITAL LABORATORIES AND SIMULATORS IN THE TRAINING OF FUTURE BIOLOGISTS: EXPERIENCE AND RESULTS ACCORDING TO TIMSS AND PISA DATA - Raupova Mehrinigor Khaidarovna (Web of Journals Publishing, 2025)
The article examines the effectiveness of introducing digital laboratories and simulators into the educational process of biologists through the prism of international TIMSS and PISA studies. The key advantages of virtual experimental environments are analyzed, correlations between the intensity of use of digital tools and students' academic achievements are revealed. Special attention is paid to the adaptation of educational programs to the requirements of modern science and practical recommendations for the integration of digital technologies into biological education.
Keywords: digital laboratories, educational simulators, training of biologists, TIMSS, PISA, innovative technologies, digitalization of education, learning outcomes, biology.